Aplicación de terapia pasiva en paciente femenino de 26 años con problemas vergenciales y acomodativos. - Gonzabay Carpio, Tamara Yoselyn (2022)
Today there are many problems that cause visual impairment, one of those many produces visual stress which will alter our binocular vision and this in turn will result in an insufficiency of vergences and excess of accommodation, which even having the best visual correction will cause symptoms such as: Asthenopia, headache, diplopia, cervical pain, poor concentration. The treatment consists of counteracting these symptoms and improving binocular vision, there are several ways to achieve this and it is through therapies, either active with exercises or passive with prisms. In this case, passive therapy was applied using twin prisms. The twin prisms will cause changes in the peripheral and central visual field of the patient, therefore a change will be achieved in the kinesthetic, proprioceptive and vestibular perceptual systems. Objective: To determine the symptomatology of the patient despite being with the best correction, theoretically base the scientific bases and make the diagnosis of the clinical case. Methodology: Inductive, deductive method was applied, analysis of the patient's data, she was referred to an ophthalmologist who confirmed tarsal conjunctival hyperemia plus 5mm mydriatic pupils in both eyes. Results: The patient reported symptoms such as asthenopia, headache, diplopia, cervical pain, poor concentration, and ocular itching. The clinical study included complementary tests to assess binocular vision, among them are amplitude of accommodation, accommodative flexibility, ppc, phoria and vergence. Conclusions: 3 upper vertical base prismatic diopters (twin prisms) were adapted, with which I counteract the symptoms.